Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen (Studi Kasus Pada Coffee Shop di Kota Bogor) - Mush’ab Ihsan Mu’tashim; Alim Setiawan Slamet (Jurnal Manajemen dan Organisasi, 2019)
This study aims to determine the effect of product quality and service quality on the customer satisfaction at Ngopi Doeloe, Popolo Coffee, Ranin Coffee House, Starbucks Coffee, The Coffee Bean & Tea Leaf, and JCo Donuts & Coffee Bogor. This research conducted by distributing questionnaires to 366 coffee shop visitors. Data analysis method used in this research is Structural Equation Model (SEM). Overall, in this reasearch found that product quality and service quality have impact on costumer satisfaction, but for the low income respondent (below Rp 3.000.000,00) the product quality variable have no impact on costumer satisfaction.